Oman in the Third Millennium BCE - Hastings , A.; Humphries , J. H.; Meadow , R. H. (The Journal of Oman Studies, 1975)
In the course of two seasons of survey the Harvard Archaeological group has located seventeen settlements which, on the basis of associated ceramics, stone structures, lithic and copper remains, can best be attributed to the Third Millennium BCE. From the accumulated evidence, a preliminary idea of the conditions of life in Bronze Age Oman can be gleaned.